Copper nanoparticles prepared by pulsed exploding wire - Humud, Hammad R. (Iraqi Journal of Physics, 2019)
In this work copper nanopowder was created at different liquid medias like DDDW, ethylene glycol and Polyvinylpyrrolidone (PVP). Copper nanopowder prepared using explosion wire process and investigated the effects of the exploding energy, wire diameter, the type of liquid on the particle size, and the particles size distribution. The nanoparticles are characterized by x-ray diffraction, UV-visible absorption spectroscopy and transmission electron microscopy (TEM). The x-ray diffraction results reveal that the nanoparticles continue to routine lattice periodicity at reduced particle size. The UV-Visible absorption spectrum of liquid solution for copper nanoparticles shows sharp and single surface Plasmon resonance (SPR) peak centered at a wavelength of 590 nm in ethylene glycol media, but don’t have peak in PVP fluid. This peak indicated the production of pure and spherical copper nanoparticle.